New AODV based clustering routing strategy - ZHENG Kai1; WANG Neng1; LIU Ai-fang2 (Tongxin xuebao)
A new AODV based clustering routing protocol（AODV-clustering）was proposed which kept the good features of AODV and also effectively solved its scalability problem.We have implemented it using Java on JiST/SWANS platform,and presenting a simulation-based evaluation,the results confirmed the effectiveness of our design